Lower Healthcare Access and Its Association With Individual Factors and Health-Related Quality of Life in Adults With Rare Diseases in Switzerland - Susanne Wehrli; Susanne Wehrli; Susanne Wehrli; Andrew A. Dwyer; Andrew A. Dwyer; Matthias R. Baumgartner; Matthias R. Baumgartner; Carmen Lehmann; Markus A. Landolt; Markus A. Landolt; Markus A. Landolt (Frontiers Media S.A., 2024)
ObjectivesThis study aims to determine clusters of access to healthcare among adults with rare diseases in Switzerland, identify associated individual characteristics of access, and impact on health-related quality of life (HRQoL).MethodsSwiss adults (N = 341) diagnosed with a rare disease completed an online survey including the Perception of Access to Healthcare Questionnaire (PAHQ) and Short Form Health Survey (SF-12). We employed partition around medoids algorithm to identify patient clusters based on the PAHQ. Various sociodemographic/disease-related factors and HRQoL were assessed.ResultsWe identified two patient clusters: higher (n = 227) and lower access (n = 114). Significantly associated with lower access were an unstable disease course (p < 0.05), increased number of misdiagnoses (p < 0.05), and diseases affecting the nervous system (p < 0.01). Membership in the lower access cluster was significantly associated with worse HRQoL (p < 0.05).ConclusionFindings highlight the need for comprehensive assessment of healthcare access in adults with rare diseases and identifies potential targets for tailored interventions.